General Equilibrium Perspective on Twin Deficits Hypothesis: An Empirical Study with US Results - Tang, Tuck Cheong (Taylor & Francis, 2015)
Abstract: This study proposes an alternative analytical framework for testing the so-called twin deficits hypothesis from the general equilibrium perspective. The income–expenditure equilibrium takes both the behavioural relationships of the saving and investment into consideration. The empirical results of cointegration tests show that the US fiscal balance, current account balance, real income and interest rates (short- and long-run) are co-movement for the observed periods between 1970Q2 and 2011Q4. Also, the causality tests suggest that budget deficit does indirectly Granger-cause current account deficit via short-run interest rate and real income. The real income and interest rates variables determining the behavioural relationships are important in understanding the US twin deficit slogan. In short, the empirical results validate the twin deficits hypothesis in the USA. Some policy implications have been drawn, especially on the implementation of the “fiscal cliff” policy. This study also recommends portfolio balance approach for future twin deficits research.